Pengungkapan Islamic Social Reporting sebagai Kepatuhan Pelaporan Prinsip Syariah Perusahaan di Sektor JII70 Tahun 2018-2022 - Kesnawati Melly Astuti; Putra, Trischa Relanda (Jurnal Iqtisaduna, 2024)
This research was conducted to find the disclosure of Islamic Social Reporting (ISR) as reporting compliance with sharia principles. Descriptive method is used in this research with quantitative approach, then content analysis testing is done by applying six indicators consisting of; products and services, environment, employees, community, and corporate governance of funding and investment. The 37 companies involved in this study were selected using purposive sampling method with the benchmark of companies listed on the Jakarta Islamic Index 70 (JII70) from 2018 to 2022 consecutively. Secondary data was used in the study by downloading the company's financial statements on the Indonesia Stock Exchange website and or related companies. This study shows that the ISR criteria are not suitable for all companies, especially on the criteria for the halal status of products. Because these criteria can only be done by companies that run their business in the food and beverage sector or companies that produce consumer goods. Meanwhile, companies that run their business in the property sector and others cannot disclose the halal status of products. With this research, researchers hope that companies listed on the Jakarta Islamic Index 70 will pay more attention to ISR disclosure in order to increase consumer confidence in the company's compliance with sharia principles.